Collective versus Decentralized Wage Bargaining and the Efficient Allocation of Resources - Xiaoming Cai; Pieter A. Gautier; Makoto Watanabe (Center for Economic Studies and ifo Institute (CESifo), 2015)
An advantage of collective wage agreement is that search and business-stealing externalities can be internalized. A disadvantage is that it takes more time before an optimal allocation is reached because more productive firms (for a particular worker type) can no longer signal this by posting higher wages. Specifically, we consider a search model with two sided heterogeneity and on-the-job search. We compare the most favorable case of a collective wage agreement (i.e. the wage that a planner would choose under the constraint that all firms in a sector-occupation cell must offer the same wage) with the case without collective wage agreement. We find that collective wage agreements are never desirable if firms can commit ex ante to a wage and only desirable if firms cannot commit and the relative efficiency of on the job search to off- the job search is less than 20%. This result is hardly sensitive to the bargaining power of workers. Empirically we find both for the Netherlands and the US that this value is closer to 50%.
Keywords: E24; J62; J63; J64; 330